KEHIDUPAN KONTEMPORER DALAM WACANA EKSISTENSIALISME MARTIN HEIDEGGER - Ahmad Rifai Abun; Jamhari Jamhari; Muhammad Hidayaturrohim (Jurnal Ilmu Agama: Mengkaji Doktrin, Pemikiran, dan Fenomena Agama, 2019)
Contemporary life is coloured with various conveniences. But the convenience is not obtained for free, but must be accompanied by various kinds of problems. Contemporary humans move in a worrying direction and require philosophical reorientation. Through a descriptive analysis approach, this paper explains how to find the format of solutions to contemporary problems through philosophical reorientation with Martin Heidegger's existentialism discourse.